Intervención psicopedagógica mediante el programa Juego de Pistas para desarrollar las habilidades sociales y comunicacionales en un niño con Trastorno del Espectro Autista (TEA) de tercer grado de la Escuela Municipal Héroes del Cenepa, 2024-2025 - Cacay Vivanco, Rosa del Cisne (2025)
The present study denominated Psychopedagogical intervention through the Game of Clues program to develop social and communication skills in a child with Autism Spectrum Disorder (ASD) of third degree of the School Municipal Heroes of the Cenepa, 2024-2025, has as its ma_>_>in objective to implement an intervention proposal through activities of the Game of Clues program in a child with ASD, the research was carried out under the qualitative approach, descriptive and cross-sectional, the sychopedagogical form, semi-structured interviews, the GARS3S test, and the learning achievement form were applied. In the methodological process, an initial evaluation was carried out to analyze the areas of communication and social interaction, evidencing a level 2 of severity, which indicated the need for substantial support, in interaction, communication, emotional response and maladaptive speech. In the pre-test, the child obtained an index of 92, corresponding to this level of severity. After the intervention with the Game of Clues program, the post-test was immediately applied, a significant improvement was observed, reducing its index to 66, corresponding to level 1 of severity, which implies that it now requires minimal support. This result reflects a considerable reduction in communication and social interaction difficulties, confirming that the intervention was effective in enhancing these skills. However, although the program demonstrated a positive impact through observations and daily logs, its scope is limited due to the more profound barriers of Level 2 ASD. Therefore, it is concluded that it is necessary to complement this type of intervention with additional strategies tailored to the child's specific needs to achieve more significant improvements